Is it safe to cross? Identification of trains and their approach speed at level crossings. (March 2018) - Larue, Grégoire S.; Filtness, Ashleigh J.; Wood, Joanne M.; Demmel, Sébastien; Watling, Christopher N.; Naweed, Anjum; Rakotonirainy, Andry
Highlights: Drivers' perceptions of oncoming trains and crossing decision making were examined. Drivers identified trains' presence 2 km away and their movement 1.6 km away. High variability was found between participants. Speed of oncoming trains was largely underestimated, particularly at higher speeds. Abstract: Improving the safety at passive rail crossings is an ongoing issue worldwide. These crossings have no active warning systems to assist drivers' decision-making and are completely reliant on the road user perceiving the approach of a train to decide whether to enter a crossing or not. This study aimed to better understand drivers' judgements regarding approaching trains and their perceptions of safe crossing. Thirty-six participants completed a field-based protocol that involved detecting and judging the speeds of fast moving trains. They were asked to report when they first detected an approaching train, when they could first perceive it as moving, as well as providing speed estimates and a decision regarding when it would not be safe to cross. Participants detected the trains ∼2 km away and were able to perceive the trains as moving when they were 1.6 km away. Large differences were observed between participants but all could detect trains within the range of the longest sighting distances required at passive level crossings. Most participants greatly underestimated travelling speed by at least 30%, despite reporting high levels of confidence in their estimates. Further, most participants would have entered the crossing at a time when the lights would have been activated if the level crossing had been protected by flashing lights. These results suggest that the underestimation of high-speed trains could have significant safety implications for road users' crossing behaviour, particularly as it reduces the amount of time and the safety margins that the driver has to cross the rail crossing.